Long-term stability of money demand and monetary policy in Indonesia - Agustantira, Vinna; Asngari, Imam; Andaiyani, Sri (Universitas Ahmad Dahlan, 2024)
The purpose of this study is to determine the long-term and short-term relationship between inflation, interest rates, exchange rates, and economic growth to the demand for money in Indonesia. The method used in this study is Autoregressive Distributed Lag (ARDL). The Data used are money demand, inflation, interest rates, exchange rates, GDP in Indonesia for the period 2015-2021. The results of this study are inflation has a positive relationship and significantly affects the demand for money, interest rates have a negative relationship and does not affect significantly, the exchange rate has a positive relationship, while GDP has a positive relationship in the short term, but in the long term has a negative relationship and does not affect significantly. Policymakers should develop and implement comprehensive long-term economic plans that prioritize sustainable growth. This may include initiatives to diversify the economy, enhance productivity, improve infrastructure, and promote investments to foster a stable economic environment that minimizes adverse effects on the demand for money in the long run. This research can help monetary authorities determine appropriate policies to maintain economic stability, such as collaborating with the government in overcoming market failures with the aim of achieving price stability.